Mathematical theory and computational practice: 5th Conference on Computability in Europe, CiE 2009, Heidelberg, Germany, July 19-24, 2009. Proceedings - Ambos-Spies, Klaus; Löwe, Benedikt; Merkle, Wolfgang (Lecture notes in computer science, 2009)
First-Order Universality for Real Programs -- Skolem + Tetration Is Well-Ordered -- Structures of Some Strong Reducibilities -- Complexity of Existential Positive First-Order Logic -- Stochastic Programs and Hybrid Automata for (Biological) Modeling -- Numberings and Randomness -- The Strength of the Grätzer-Schmidt Theorem -- Hyperloops Do Not Threaten the Notion of an Effective Procedure -- Minimum Entropy Combinatorial Optimization Problems -- Program Self-reference in Constructive Scott Subdomains -- and Equivalence Structures -- Immunity for Closed Sets -- Lower Bounds for Kernelizations and Other Preprocessing Procedures -- Infinite-Time Turing Machines and Borel Reducibility -- Cutting Planes and the Parameter Cutwidth -- Members of Random Closed Sets -- Lowness for Demuth Randomness -- Graph States and the Necessity of Euler Decomposition -- On Stateless Multicounter Machines -- Computability of Continuous Solutions of Higher-Type Equations -- Equivalence Relations on Classes of Computable Structures -- Fractals Generated by Algorithmically Random Brownian Motion -- Computable Exchangeable Sequences Have Computable de Finetti Measures -- Spectra of Algebraic Fields and Subfields -- Definability in the Local Theory of the ?-Enumeration Degrees -- Computability of Analytic Functions with Analytic Machines -- An Application of Martin-Löf Randomness to Effective Probability Theory -- Index Sets and Universal Numberings -- Ordinal Computability -- A Gandy Theorem for Abstract Structures and Applications to First-Order Definability -- Constructing New Aperiodic Self-simulating Tile Sets -- Relationship between Kanamori-McAloon Principle and Paris-Harrington Theorem -- The First Order Theories of the Medvedev and Muchnik Lattices -- Infima of d.r.e. Degrees -- A Divergence Formula for Randomness and Dimension -- On Ladner’s Result for a Class of Real Machines with Restricted Use of Constants -- 0?-Categorical Completely Decomposable Torsion-Free Abelian Groups -- Notes on the Jump of a Structure -- A General Representation Theorem for Probability Functions Satisfying Spectrum Exchangeability -- Stability under Strategy Switching -- Computational Heuristics for Simplifying a Biological Model -- Functions Definable by Arithmetic Circuits -- Survey on Oblivious Routing Strategies -- An Approach to the Engineering of Cellular Models Based on P Systems -- Decidability of Sub-theories of Polynomials over a Finite Field -- Chaitin ? Numbers and Halting Problems -- Bayesian Data Integration and Enrichment Analysis for Predicting Gene Function in Malaria -- Dialectica Interpretation with Fine Computational Control -- Algorithmic Minimal Sufficient Statistic Revisited -- A Computation of the Maximal Order Type of the Term Ordering on Finite Multisets -- On Generating Independent Random Strings.
Keywords: Konferenzschrift -- 2009 -- Heidelberg; Berechenbarkeit